1985
DOI: 10.1177/001698628502900404
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of Gifted Students for Selected Teacher Characteristics

Abstract: Gifted children in grades 7-9 (N = 98) judged the importance of selected teacher characteristics in personal-social, cognitive, and classroom management domains. Subjects were enrolled in a gifted program in a large junior high school in West Texas. Gifted children were found to prefer personal-social characteristics over cognitive or classroom management characteristics. Results were compared to findings of a similar study conducted in Israel in which cognitive characteristics were found to be most highly val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 3 publications
3
14
0
Order By: Relevance
“…Findings show that gifted students consider personal-social characteristics to be more important than cognitive-intellectual characteristics. It is seen that gifted students prefer personal-social characteristics more in studies about gifted students across different countries (Abel & Karnes, 1994;Dorhout, 1983;Maddux et al, 1985;Rosemarin, 2009;Vialle & Tischler, 2005). Preferences of characteristics that students want their teachers to possess do not differ in terms of gender.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Findings show that gifted students consider personal-social characteristics to be more important than cognitive-intellectual characteristics. It is seen that gifted students prefer personal-social characteristics more in studies about gifted students across different countries (Abel & Karnes, 1994;Dorhout, 1983;Maddux et al, 1985;Rosemarin, 2009;Vialle & Tischler, 2005). Preferences of characteristics that students want their teachers to possess do not differ in terms of gender.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…This new role firstly requires closer relations compared to the past (Rosemarin, 2009, 53). Closer relations lead to closer interactions, but first of all, a teacher must have a wide range of characteristics; and these characteristics are classified in some studies as personal-social, cognitive-intellectual and pedagogical/classroom management (Eilam & Vidergor, 2011;Maddux, Samples-Lachmann, & Cummings, 1985). In other studies; pedagogical/classroom management is not classified as a different characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…However, the findings may be compared in part with the rather mixed outcomes of international studies which include those of Milgram (1978) who found intelligence to be valued over personality and creativity by both gifted and nongifted students, while Maddux, Samples-Lachmann and Cummings (1985) found the gifted favoring personal-social characteristics (though they noted the highly gifted valued cognitive variables more) and Roberts, Carter and Mosley (1982) reported that for gifted students the teacher's willingness to help was most important.…”
Section: Student Perceptions Of Important Qualities In Teachersmentioning
confidence: 98%
“…In several studies (Freehill, 1974;Hansford, 1985;Newland, 1962;Torrance and Myers, 1978), gifted teachers were found to be characterized by emotional security, positive sense of self, superior intelligence, curiosity, cognitive agility, openness, flexibility, strong communication skills, and a constant search for new experiences. Gifted teachers were also found to have a sense of mission, empathy, drive, rapport, enthusiasm, creativity, high expectations, frequent innovations, and respect for students (Dorhout, 1983;Ferrel, Kress, and Croft, 1988;Maddux, Samples-Lachmann, and Cumming, 1985;Renzulli, 1969;Wendel and Helser, 1989 Some of these actions were also included in Mullen's (2005) analysis of "alternative mentors" who "strive to make a profound difference in the development of students, colleagues, and others" and "mentor beyond the demands of their position, seeking to enhance the development and education of protégés outside the traditional supervisory or advisory context" (p. 37). Mullen recognized that mentoring is a "separate or superordinate function because it requires an 'above and beyond' effort" (p.37).…”
Section: Gifted Mentorshipmentioning
confidence: 99%